Formulation and Evaluation of Nystatin Microparticles as a Sustained Release System - Sara T.Ismail; Myasar M. Al-Kotaji; Ahlam A. Khayrallah (College of Pharmacy University of Baghdad, 2017)
Nystatin is the drug of choice for treatment of cutaneous fungal infections with main disadvantage that is the need for multiple applications to achieve complete eradication which may reduce patient compliance. Microparticles offer a solution for such issue as they are one of sustained release preparations that achieve slow release of drug over an extended period of time. The objectives of this study were to fabricate nystatin-loaded chitosan microparticles with the ultimate goal of prolonging drug release and to analyze the influence of polymer concentration on various properties of microparticles. Microparticles were prepared by chemical cross-linking method using glutaraldehyde as cross-linking agent. Five formulas, namely N1C1, N1C2, N1C3, N1C4 and N1C5, were prepared and the effect of drug to polymer ratio was studied with respect to drug loading, encapsulation efficiency, particle size and morphology. Furthermore the prepared microparticles were subjected to various physico-chemical studies, such as drug- polymer compatibility by Fourier Transform Infrared Spectroscopy (FTIR) and in-vitro drug release characteristics. Microparticles obtained from N1C1, N1C2 and N1C3 formulas were regular in shape with mean particle size ranging between 1Âµm and 10Âµm. N1C5 formula was resulted in particles with irregular shape while N1C4 showed a blend of microparticles and deformed particles. The effect of chitosan concentration on drug loading and entrapment efficiency was studied. The results showed increment in these parameters that was directly proportional to the increment in polymer concentration. Percentage yield showed a significant increment which was related to the increment in the ratio of chitosan used during the study. FTIR results showed no interactions between nystatin and chitosan. DSC studies proved the crystalline nature of nystatin and chitosan. On other hand, the thermogram of loaded microparticles showed the absence of endothermic peak corresponding to nystatin which may indicate the loss of the crystalline nature of the drug presented inside the microparticles. In- vitro release studies resulted in 95.6% release of nystatin for N1C1 after 15 hours. N1C1 appeared to be promising in formulating microparticles that provide nearly complete release of the drug within15 hours. This formula can be selected in future work to be formulated as topical gel that prolongs the release of nystatin. Keywords: Nystatin, Chitosan, Glutaraldehyde, Chemical cross-linking.